Young People As Agents of Sustainable Society : Reclaiming the Future. - Honkatukia, Päivi.; Rättilä, Tiina (Milton : Taylor & Francis Group, 2023)
This book analyses young people's societal participation as a central dimension of their wellbeing, and as vitally important to secure the sustainable future of humankind and the whole eco-social system.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books